An optimum watershed management system and a method thereof. - Mohd Soom, Mohd Amin; Al-Ansi, Abdul Wahab Mujahed; Ghazali, Abdul Halim; Mohd Shafri, Helmi Zulhaidi; Wayayok, Aimrun (2010)

(untitled)
An optimum watershed runoff management system (100) for controlling floods and base flow and a method thereof is provided, characterized in that, the system (100) includes at least one input source (110), a modeling means (120), at least one output (140) and a database (150), wherein theat least one input source (110), the modeling means (120), the at least one output (140) and the database (150) are network connectable, wherein a plurality of data (160) is processable using the modeling means (120) to produce the at least one output (140).